Antiproton, proton and electron impact multiple ionization of rare gases - Montanari, Claudia Carmen (2012)
We present a study on multiple ionization of Ne, Ar, Kr and Xe by antiproton, proton and electron impact. Four different aspects are involved in this work. First, the theoretical calculations of ionization probabilities by impact of antiprotons and protons, in an extended energy region (25 keV to 10 MeV), using the continuum distorted-wave eikonal initial state approximation and the first Born approximation. Second, the inclusion of Auger-type post-collisional contributions through experimental photoionization branching ratios. These contributions to multiple ionization are very important in the high-energy region. Third, the comparison with the available experimental data on multiple ionization by protons and antiprotons in the extended energy range, and by electrons for high-impact velocities, where proton, antiproton and electron impact results are expected to converge. It is also the energy region where direct ionization does not explain the experimental results, and the post-collisional ionization is the main contribution to multiple ionization. And fourth, total ionization cross sections are calculated and compared with the antiproton, proton and electron experimental data, showing the importance of Auger-type multiple ionization for heavy targets even at the level of total cross sections. Gross and count cross sections are scrutinized.